Symmetry-breaking orbital anisotropy observed for detwinned Ba(Fe1-xCox)₂As₂ above the spin density wave transition - Yi, Ming; Lu, Donghui; Chu, Jiun-Haw; Analytis, James G.; Sorini, Adam P.; Kemper, Alexander F.; Moritz, Brian; Mo, Sung-Kwan; Moore, Rob G.; Hashimoto, Makoto; Lee, Wei-Sheng; Hussain, Zahid; et al. (Proceedings of the National Academy of Sciences - PNAS, 2011)
Nematicity, defined as broken rotational symmetry, has recently been observed in competing phases proximate to the superconducting phase in the cuprate high-temperature superconductors. Similarly, the new iron-based high-temperature superconductors exhibit a tetragonal-to-orthorhombic structural transition (i.e., a broken C₄ symmetry) that either precedes or is coincident with a collinear spin density wave (SDW) transition in undoped parent compounds, and superconductivity arises when both transitions are suppressed via doping. Evidence for strong in-plane anisotropy in the SDW state in this family of compounds has been reported by neutron scattering, scanning tunneling microscopy, and transport measurements. Here, we present an angle-resolved photoemission spectroscopy study of detwinned single crystals of a representative family of electron-doped iron-arsenide superconductors, Ba(Fe1-xCox)₂As₂ in the underdoped region. The crystals were detwinned via application of in-plane uniaxial stress, enabling measurements of single domain electronic structure in the orthorhombic state. At low temperatures, our results clearly demonstrate an in-plane electronic anisotropy characterized by a large energy splitting of two orthogonal bands with dominant dxz and dyz character, which is consistent with anisotropy observed by other probes. For compositions x > 0, for which the structural transition (Ts) precedes the magnetic transition (TSDW), an anisotropic splitting is observed to develop above TSDW, indicating that it is specifically associated with TS. For unstressed crystals, the band splitting is observed close to Ts. whereas for stressed crystals, the splitting is observed to considerably higher temperatures, revealing the presence of a surprisingly large in-plane nematic susceptibility in the electronic structure.